Probing the mechanism of the interaction between l‐cysteine‐capped‐CdTe quantum dots and Hg2+ using capillary electrophoresis with ensemble techniques. Issue 6 (March 2015) - Xu, Laifang; Hao, Junjie; Yi, Tao; Xu, Yinyin; Niu, Xiaoying; Ren, Cuiling; Chen, Hongli; Chen, Xingguo
<x xml:space="preserve">Abstract</x> The mechanism of the interaction between quantum dots (QDs) and heavy metal ions was probed by capillary electrophoresis (CE) and other ensemble methods. Three different Hg2+/L‐cys‐CdTe QDs ratios were selected to investigate the interaction behavior. The effects of the free and capping ligands on the system are discussed. Two different binding products, the static complex (QDs‐Hg2+ complex) and the Hg2+‐L‐cys complex, were found to be dependent on Hg2+ concentration. Electrophoresis 2015, 36, 859–866. DOI: 10.1002/elps.201400509<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>